Glycogen supercompensation enhances athletic performance - Prevost, M. C.
The glycogen supercompensation effect (achieving supraphysiological glycogen levels due to carbohydrate depletion followed by loading) was first demonstrated in 1967. Since that time it has become a very popular pre-event performance enhancing strategy. Endurance athletes benefit from glycogen supercompensation because fatigue in events lasting longer than one hour is related primarily to glycogen depletion. Bodybuilders benefit from glycogen supercompensation because each gram of glycogen is stored with 3 grams of water; therefore a doubling in glycogen stores can increase the bodybuilder`s apparent muscle mass. Glycogen supercompensation is probably of little use to power athletes since fatigue in these events is not related to glycogen depletion and the weight gain may be a liability. Glycogen supercompensation occurs only when a low carbohydrate diet is combined with vigorous exercise followed by a high carbohydrate diet. Glycogen supercompensation occurs only in muscles that were trained and is maximal at a carbohydrate intake of approximately 25 grams per hour for average adults and possibly 40 grams or more per hour for bodybuilders.